The prevalence of pterygium in Al-Khobar: A hospital-based study - Jerman M Alqahtani (Wolters Kluwer Medknow Publications, 2013)
Objective: To analyze the epidemiology of pterygium in a hospital-based population in Al-Khobar, which is located in the eastern province of Saudi Arabia. Materials and Methods: This was a retrospective, non-randomized, and consecutive case study. Out of 88,666 patients who were seen in the ophthalmology clinic between January 1995 through the end of December 2010, 116 patients were diagnosed with advanced pterygium. The medical records of these patients were evaluated. Results: The overall prevalence of pterygium was found to be 0.074%. There was no significant difference by either gender, side, or by laterality (P > 0.05). A significant increase was noticed in the prevalence of pterygium with increasing age and nasal location (P < 0.05). Conclusion: The overall prevalence rate of pterygium in Al-Khobar is low when compared with results reported from other areas of the world.